Sleep Difficulties Among COVID-19 Frontline Healthcare Workers - Cleper, Rony; Hertz-Palmor, Nimrod; Mosheva, Mariela; Hasson-Ohayon, Ilanit; Kaplan, Rachel; Kreiss, Yitshak; Afek, Arnon; Pessach, Itai M.; Gothelf, Doron; Gross, Raz (Frontiers in Psychiatry, 2022)
Objective: To identify COVID-19 work-related stressors and experiences associated with sleep difficulties in HCW, and to assess the role of depression and traumatic stress in this association. Methods: A cross-sectional study of HCW using self-report questionnaires, during the first peak of the pandemic in Israel (April 2020), conducted in a large tertiary medical center in Israel. Study population included 189 physicians and nurses working in designated COVID-19 wards and a comparison group of 643 HCW. Mean age of the total sample was 41.711.1, 67% were female, 42.1% physicians, with overall mean number of years of professional experience 14.220. The exposure was working in COVID-19 wards and related specific stressors and negative experiences. Primary outcome measurement was the Insomnia Severity Index (ISI). Secondary outcomes included the Primary Care-Post Traumatic Stress Disorder Screen (PC-PTSD-5); the Patient Health Questionnaire-9 (PHQ-9) for depression; the anxiety module of the Patient-Reported Outcomes Measurement Information System (PROMIS); Pandemic-Related Stress Factors (PRSF) and witnessing patient suffering and death. Results: Compared with non-COVID-19 HCW, COVID-19 HCW were more likely to be male (41.3% vs 30.7%) and younger (36.91±8.81 vs 43.14±11.35 years). COVID-19 HCW reported higher prevalence of sleep difficulties: 63% vs 50.7% in the non-COVID group (OR 1.62, 95% CI 1.15-2.29, p=0.006), mostly difficulty maintaining sleep: 26.5% vs 18.5% (OR 1.65, 95% CI 1.11-2.44, p=0.012). Negative COVID-19 work-related experiences, specifically witnessing patient physical suffering and death, partially explained the association. Although past psychological problems and current depression and PTSD were associated with difficulty maintaining sleep, the main association remained robust also after controlling for those conditions in the full model. Conclusions and Relevance: COVID-19 frontline HCW were more likely to report sleep difficulties, mainly difficulty maintaining sleep, as compared with non-COVID-19 HCW working at the same hospital. Negative patient-care related experiences likely mediated the increased probability for those difficulties. Future research is needed to elucidate the long-term trajectories of sleep difficulties among HCW during large scale outbreaks, and to identify risk factors for their persistence.